IMPEMENTASI KEBIJAKAN PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA PEKANBARU - Muhamad Sobri Ardika; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Regional governments have great authority in exploring their own financial resources to be able to carry out regional autonomy that is broad, real and responsible. One of the financial sources that can be developed by local governments is local taxes which are a component of local revenue (PAD). Pekanbaru City where as the capital of Riau Province which is developing towards a metropolitan area has active population mobility both in various trade and industrial businesses, so that the tax sector is a potential source of income for regional development, especially advertisement tax, but in reality in recent years the tax realization advertisements have not reached their targets, therefore it is necessary to implement appropriate advertisement policies in increasing local revenue, especially advertisement tax. The purpose of this study was to identify and analyze the implementation of advertising tax policies in increasing regional own-source revenue in Pekanbaru City and to determine the factors that influence the implementation of advertisement tax policies in increasing regional ownsource revenue in Pekanbaru City. The urgency of this research is that it is hoped that it can be a solution and input for Bapenda in implementing advertising policies in Pekanbaru City and increasing regional income for better regional development. The research method used is qualitative. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this study concluded that the implementation of the Advertising Tax Area Original Revenue Increase Program in Pekanbaru City had been carried out properly with reference to regional tax regulations and regional income increase programs compiled and determined by the Pekanbaru City Regional Revenue Agency, regarding the size and objectives that had been contained in the policy. and programs, resources that have been set and provided by the City government, a clear bureaucratic structure, inter-line communication and a conducive environment to realize the realization according to the targets set, the Implementation of the Advertising Tax Area Original Income Increase Program in Pekanbaru City is in the category enough done Keywords: Implementation, program, Increasing Regional Original Income, taxes, billboards